Too Muslim or not Muslim enough? Exploring identity negotiations for women visual artists in Australia. (March 2023) - Ralph, Elizabeth; Gibson, Margaret
The title of this article is deliberately provocative aiming to trouble the imposition of identity fixations and reductive assumptions on creative endeavours and outputs. This article is based on a research project which investigated the identity negotiations and representational responsibilities of women visual artists of Muslim faith and/or cultural background practising and exhibiting their artwork in Australia. This article shows how artists sometimes embrace certain identity markers in order to gain opportunities and promote forms of visibility and debate. At the same time, artists can feel the limitations of being pigeonholed and scrutinised because they have not met the normative and moral expectations of their cultural and religious communities as well as those of communities and organisations associated with the arts sector they have been associated with or with which they may wish to have a future association.